Immunogenic chemotherapy effectively inhibits KRAS-Driven lung cancer. (1st November 2020) - Wang, Dong; Cong, Jingjing; Fu, Binqing; Zheng, Xiaohu; Sun, Rui; Tian, Zhigang; Wei, Haiming
Abstract: Immunogenic chemotherapy has been shown to be effective against several cancer types. Here, we identified trametinib as an inducer of immunogenic cell death (ICD), and found that it exerts beneficial antitumor effects if used in combination with interleukin (IL)-12 in a Kras -mutant mouse model of spontaneous lung cancer. Tumor cells treated with trametinib showed the hallmarks of ICD, including cell-surface expression of calreticulin, release of high mobility group box 1 (HMGB1) from the nucleus, and activation of dendritic cells. Tumor-bearing mice treated with both trametinib and IL-12 showed increased infiltration and proliferation of T cells within the tumor, as well as increased effector function of NK cells and T cells, indicating that this therapeutic combination can improve the quality of the immune response. Taken together, our results provide a potential new therapeutic regimen for the treatment of KRAS -mutant lung adenocarcinomas. Highlights: Trametinib can act as an ICD inducer on lung cancer cells. Trametinib combined with IL-12 restrains the progression of Kras driven lung cancer efficaciously. Trametinib combined with IL-12 increases the effector function of NK and T cells significantly.